New orientation formation and growth during primary recrystallization in stable single crystals of three face-centred cubic metals. (15th January 2015) - Miszczyk, M.; Paul, H.; Driver, J.H.; Maurice, C.
Graphical abstract: For Ni, Cu and Cu-2%Al and (1 1 0)[0 0 −1] and (1 1 0)[1 −1 −2] initial orientations at the initial stages of recrystallization, the appearance of a specific number of new orientation groups of new grains has been demonstrated. The orientation relations across the recrystallization front are characterized by a high proportion of angles in the range 25–35° and 45–55° around axes mostly grouped about the 〈1 2 2〉, 〈1 1 1〉, 〈1 2 3〉 and 〈1 1 2〉 directions. A local minimum was noted for the disorientation angle densities close to 40° in all cases. For a single isolated nucleus of uniform orientation, the rotation axes are usually grouped around one of the normals of all four 1 1 1 planes but do not (or only rarely) coincide with them. The orientation of the growing new grain quickly transforms through the formation of a first generation twins. The most frequent situation occurs when the normal of the twinning face plane is situated near the rotation axis, around which the crystal lattice of the 'primary nuclei' rotates. Based on the anisotropy of grain growth a possible mechanism of orientation generation and grain growth by thermally activation movement of dislocation families, on 1 1 1 planes is proposed. Abstract: The early stages of recrystallization have been systematically characterized in single crystal metals of medium and low stacking fault energy. Goss 1 1 0〈0 0 1〉 and brass 1 1 0〈1 1 2〉 oriented samples of Ni, Cu and Cu–2 wt.% Al alloy were deformed in a channel die to a logarithmic strain of 0.51 to develop a homogeneous structure composed of two sets of symmetrical primary microbands and then lightly annealed. Scanning electron microscopy/electron backscattered diffraction analyses demonstrate a strong relation between as-deformed orientations and the limited number of recrystallized grain orientations. The disorientation angles across the recrystallization front are mostly grouped in the ranges of 25–35° and 45–55° around axes located near, but not at, the normals of all four 1 1 1 planes. The original nuclei possess disorientation angles of 25–35°. The orientation of the growing new grain quickly transforms through the formation of a first generation twin, leading to disorientations of 45–55°. The most frequent situation occurs when the normal of the twinning face plane is situated near the rotation axis, around which the crystal lattice of the "primary nuclei" rotates. Based on the anisotropy of grain growth, a possible mechanism of orientation generation and grain growth by thermally activated movement of dislocation families on 1 1 1 planes is proposed.